Mechanism and criteria of dilatancy-induced disaster of coal containing gas - Hu, Z.; Wu, S.; Yin, Zhiqiang (2017)
© 2017 Eastern Macedonia and Thrace Institute of Technology. The key to the prevention and control of coal and gas dynamic disaster is the mastery of its mechanism. However, plenty of factors induce coal and gas dynamic disasters, and the mechanism is complex, especially the dilatancy of coal and rock by mining. The main control factors of dynamic disasters change, thereby making such disasters difficult to manage. The mechanism of dilatancy caused by coal crack was analyzed based on the physical mechanical characteristics of gassy coal to explore the mechanism of coal and gas dynamic disaster induced by coal dilatancy in the working face. The energy evolution characteristics of the coal face during dilatancy stage were studied, and the safety evaluation index of disaster caused by the dilatancy was presented. Results show that the coal dilatancy in the working face depends on the force environment and the physical mechanical properties of coal. With the increase in initial gas pressure, elastic modulus, compressive strength, and critical stress value of the dilatancy are reduced, resistance to deformation and destruction of the coal containing gas is weakened, and the mechanical phenomenon of dilatancy easily occurs. The change gradient of gas pressure and gas expansion energy can increase with the increase in initial gas pressure in the dilatancy moment. The safety evaluation index increases from 0.09 to 1.29 when the initial gas pressure reaches 3 MPa. This finding shows that the safety evaluation index of disaster caused by the dilatancy has a nonlinear positive correlation with gas pressure. The dynamic disaster can only be caused by the effect of the mining action at a gas pressure of 3 MPa. This study provides a theoretical reference for the prevention and control of coal and gas dynamic disasters.